Natural Selection in a Population is a Problem of Nonlinear Genetics - A.N. Volobuev (Journal of Genetic Engineering, 2019)
The problem of natural selection against recessive homozygotes in a population is investigated. It is shown that natural selection of mutant alleles linked with the Х-chromosome in a population at women is described by the nonlinear differential equation of the third order. The order of the differential equation characterizes a power of selection. It is marked that the high order of the differential equation of natural selection allows level all mutational processes in Earth populations.
Keywords: Hardy-Weinberg’s law